JUDGE DECISION AS AN ENGINEERING TOOL IN THE PREVENTION OF CORRUPTION AND MONEY LAUNDERING - Oly Viana Agustine (Asia Pacific Fraud Journal, 2016)
Preventing corruption and money laundering requires extra facilities and infrastructure, especially in the process of prosecution. Various measures have been taken by government to eradicate corruption and money laundering. Starting from anti-corruption education to the threat of death penalty for the convicted of corruption have been formulated and implemented in the Indonesian legislation. These measures, however, have not been able to provide maximum results in eradicating corruption and money laundering. Therefore, there should be several alternatives in preventing such cases by enhancing the effectiveness of the existing efforts, one of which is through judge decision. Judge decision, better known as one of the prosecution efforts, can also be made as an engineering tool to prevent corruption and money laundering. This can be seen in the Constitutional Court Decision that provides requirement restriction to the individual candidate for Regional Representative Council (DPD), House of Representatives (DPR), Regional House of Representatives either Provincial, Regency or City, regional head and deputy regional head and for ex-convict with the threat of 5 (five) years imprisonment or more, including corruption and money laundering. In addition, the United Nations Convention Against Corruption (UNCAC) has also provided guidelines on the decision against unauthorized wealth.